A study of work-related stress among nurses in a tertiary care hospital in Goa - Pai Vernekar, Shefalee; Shah, Hemangini (International Journal Of Community Medicine And Public Health, 2018)
Background: Nursing is, by its very nature, a stressful occupation. The role of nursing is associated with multiple and conflicting demands imposed by nurse supervisors and managers, and by medical and administrative staff. Such a situation appears to lead to work overload and possible to role conflict. This seriously impairs the provision of quality care and the efficacy of health services delivery. The objectives of the study were to determine the levels of work-related stress in nurses; to identify various sources of stress among nurses; to develop suitable recommendations based on the findings of the study. Methods: A cross-sectional study was conducted among registered nurses working in wards of a tertiary care hospital, Goa wherein Expanded Nursing Stress Scale was used to assess level and sources of stress among them. Results: 59.3% of nurses experienced moderate. 36.8% severe, 2.4% experienced very severe stress. Highest mean score was in the area of death and dying subscale (2.35±0.61) and workload subscale (2.11±0.53). Nurses working in casualty and general wards were more stressed. Also, younger nurses were more stressed in dealing with death of a patient. Conclusions: Death of a patient and excessive workload were major contributors of stress. Stress reduction activities and measures to decrease workload will help in decreasing the stress at workplace.